Lineage analysis of circulating Trypanosoma cruzi parasites and their association with clinical forms of Chagas disease in Bolivia. - Ramona del Puerto; Juan Eiki Nishizawa; Mihoko Kikuchi; Naomi Iihoshi; Yelin Roca; Cinthia Avilas; Alberto Gianella; Javier Lora; Freddy Udalrico Gutierrez Velarde; Luis Alberto Renjel; Sachio Miura; Hiroo Higo; et al. (Public Library of Science (PLoS), 2010)
BACKGROUND: The causative agent of Chagas disease, Trypanosoma cruzi, is divided into 6 Discrete Typing Units (DTU): Tc I, IIa, IIb, IIc, IId and IIe. In order to assess the relative pathogenicities of different DTUs, blood samples from three different clinical groups of chronic Chagas disease patients (indeterminate, cardiac, megacolon) from Bolivia were analyzed for their circulating parasites lineages using minicircle kinetoplast DNA polymorphism. METHODS AND FINDINGS: Between 2000 and 2007, patients sent to the Centro Nacional de Enfermedades Tropicales for diagnosis of Chagas from clinics and hospitals in Santa Cruz, Bolivia, were assessed by serology, cardiology and gastro-intestinal examinations. Additionally, patients who underwent colonectomies due to Chagasic magacolon at the Hospital Universitario Japonés were also included. A total of 306 chronic Chagas patients were defined by their clinical types (81 with cardiopathy, 150 without cardiopathy, 100 with megacolon, 144 without megacolon, 164 with cardiopathy or megacolon, 73 indeterminate and 17 cases with both cardiopathy and megacolon). DNA was extracted from 10 ml of peripheral venous blood for PCR analysis. The kinetoplast minicircle DNA (kDNA) was amplified from 196 out of 306 samples (64.1%), of which 104 (53.3%) were Tc IId, 4 (2.0%) Tc I, 7 (3.6%) Tc IIb, 1 (0.5%) Tc IIe, 26 (13.3%) Tc I/IId, 1 (0.5%) Tc I/IIb/IId, 2 (1.0%) Tc IIb/d and 51 (25.9%) were unidentified. Of the 133 Tc IId samples, three different kDNA hypervariable region patterns were detected; Mn (49.6%), TPK like (48.9%) and Bug-like (1.5%). There was no significant association between Tc types and clinical manifestations of disease. CONCLUSIONS: None of the identified lineages or sublineages was significantly associated with any particular clinical manifestations in the chronic Chagas patients in Bolivia.